2001
DOI: 10.1021/bi010117f
|View full text |Cite
|
Sign up to set email alerts
|

Insect Immune Activation by Apolipophorin III Is Correlated with the Lipid-Binding Properties of This Protein

Abstract: Apolipophorin III (apoLp-III) is an exchangeable insect apolipoprotein consisting of five amphipathic alpha-helices. The protein is able to open reversibly on associating with hydrophobic surfaces and plays a role both in lipid transport and induction of immune responses. Point mutations were introduced at positions 66 (N-->D) and/or 68 (K-->E) between helices 2 and 3, a region possibly serving as a hinge for the opening of the molecule when associating with lipids. The lipid-binding properties of the mutant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 27 publications
0
45
0
1
Order By: Relevance
“…This protein has been shown to increase and stimulate the immune response and its ability to stimulate an immune response is associated with its lipid binding capabilities [13]. Here there was a 5-fold decrease in the precursor form of this protein in C. albicans challenged larvae whichwould suggest that the protein's active form was increased.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 78%
See 2 more Smart Citations
“…This protein has been shown to increase and stimulate the immune response and its ability to stimulate an immune response is associated with its lipid binding capabilities [13]. Here there was a 5-fold decrease in the precursor form of this protein in C. albicans challenged larvae whichwould suggest that the protein's active form was increased.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 78%
“…Mass spectrometry analysis of tryptic-digested proteins or naturally occurring peptides (peptidomics) has also been used to quantify the changes in protein expression and the induction of novel proteins following infection [13]. Recent studies have utilised two-dimensional (2D) analysis of Drosophila haemolymph and Anopheles gambiae [14] and many groups have reported data concerning protein expression and induction in Drosophila utilising a proteomic approach [15e17].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid-associated apoLp-III complexes were synthesized for functional assays, as several reports indicated that apoLp-III functions immunologically only when bound to lipid (15,(22)(23)(24). To produce the complex, 1,2-dimyristoyl-rac-glycero-3-phosphocholine (DMPC) was incubated with apoLp-III at a ratio of 2:1, respectively, as described by Dettloff and Wiesner (15).…”
Section: Purification Of Native Apolp-iii and Lipid-associated Apolp-mentioning
confidence: 99%
“…Furthermore, apoLp-III stimulates increases in hemolymph antibacterial activity (3) and superoxide production by blood cells (hemocytes) (15). Under normal conditions in larval hemolymph, apoLp-III exists abundantly in a folded, lipid-free state (21); however, recent studies (15,(22)(23)(24) strongly suggest that lipid-free apoLp-III must first convert to a lipid-associated conformation to function immunologically, as is the case for mammalian apoE (10). Until now, however, no role has been identified for apoLp-III in the binding of ␤-1,3-glucans released systemically from fungal cell walls.…”
mentioning
confidence: 99%